2015
DOI: 10.1039/c4cc09327e
|View full text |Cite
|
Sign up to set email alerts
|

Construction of tetralin skeletons based on rhodium-catalysed site-selective ring opening of benzocyclobutenols

Abstract: Tetralins (tetrahydronaphthalenes) are synthesised from benzocyclobutenols based on the rhodium-catalysed site-selective ring opening followed by intermolecular/intramolecular conjugate addition of the resulting arylrhodium species to electron-deficient alkenes. The produced structures make a remarkable contrast with those available from the same compounds under thermal reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…4 In 2012, Murakami and co-workers reported seminal work on rhodium-catalyzed tandem C–C single bond cleavage/formal cycloaddition of benzocyclobutanols with alkynes [eqn (1)]. 4 b Since then, vinyl ketones, 5 carbene precursors, 6 and allenes 7 have been proven to be suitable cycloaddition counterparts, demonstrating the broad applicability of this protocol [eqn (2)–(4)]. However, to the best of our knowledge, under rhodium catalyzed cycloaddition with unsaturated 2-π systems, ring opening of cyclobutanols exclusively occurred on the C(sp 2 )–C(sp 3 ) bond adjacent to the hydroxyl group, with subsequent addition of the ipso carbon [ i.e.…”
Section: Introductionmentioning
confidence: 99%
“…4 In 2012, Murakami and co-workers reported seminal work on rhodium-catalyzed tandem C–C single bond cleavage/formal cycloaddition of benzocyclobutanols with alkynes [eqn (1)]. 4 b Since then, vinyl ketones, 5 carbene precursors, 6 and allenes 7 have been proven to be suitable cycloaddition counterparts, demonstrating the broad applicability of this protocol [eqn (2)–(4)]. However, to the best of our knowledge, under rhodium catalyzed cycloaddition with unsaturated 2-π systems, ring opening of cyclobutanols exclusively occurred on the C(sp 2 )–C(sp 3 ) bond adjacent to the hydroxyl group, with subsequent addition of the ipso carbon [ i.e.…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] Recently,Murakami et al and Wang et al reported the rhodium-catalyzed cyclization of BCB with alkynes or diazo esters,r espectively. [7,8] Recently,Murakami et al and Wang et al reported the rhodium-catalyzed cyclization of BCB with alkynes or diazo esters,r espectively.…”
mentioning
confidence: 99%
“…[9] We are interested in ring-fused benzocyclobutenols (RBCB) as they can be easily obtained using ao ne-step synthesis from commercially available aryl bromides and cyclic ketones. [7,11,12] We recently reported the silver-o rm anganese-catalyzed distal CÀCbond cleavage of RBCB to generate medium-sized carbocyclic fluorides or azides (Scheme 1, path (a)). Theb enzocyclobutyl C À C bond can be cleaved in "distal" or "proximal" pathway.…”
mentioning
confidence: 99%
See 2 more Smart Citations